Vibration problems of skips in mine shafts : the effect of compressive forces in the guides - Pretorius, T S (Department of Civil Engineering, 2016)
Investigations into problems involving the vibration of conveyances in deep mining shafts have led to the identification of 'slamming' as a significant event in the initiation of large perturbations in the motion of the skip. Slamming occurs when the flexible rollers on the skip which normally act on the guides are inoperative. The primary concern is that this slamming event can give rise to large lateral loads on the shaft steelwork and is therefore a factor which limits the speed at which the skip can be drawn up the shaft. This study extends previous work to investigate the influence of compressive forces in the guides on the response of the skip and the steelwork. These forces are induced as a result of mining operations and lead to a decrease in the transverse stiffness of the guides. A mathematical model of the slamming event is formulated and a numerical solution for a specific case is performed. An alternative simplified solution is discussed and compared to the initial formulation, with the aim of facilitating the use of previous research results. A model to simulate the response of the skip when the skip rollers are functional is formulated, and numerical solutions of different examples are given. An important conclusion is that the compressive forces can significantly reduce the transverse stiffness of the guides, and should be taken into account in future designs. Bibliography: pages 86-88.